Severe intravenous immunoglobulin‐induced hemolysis with pigment nephropathy managed with red cell exchange. Issue 5 (22nd August 2015) - Lasica, Masa; Zantomio, Daniela
Abstract : We report on the use of red cell exchange in a case of severe intravenous immune globulin induced hemolysis and pigment nephropathy. Renal impairment and hemoglobinuria were not ameliorated by supportive measures including hydration. Partial red cell exchange with group O blood reduced hemoglobinuria and appeared to stabilize renal function. This is the first report on the use of red cell exchange in this clinical setting. J. Clin. Apheresis 31:464–466, 2016. © 2015 Wiley Periodicals, Inc.